Otis II : light at the end of the tunnel for damages indirectly caused by competition law infringements - Venda, Sílvia Bessa (2021)
The European Court of Justice (ECJ) culminated a particularly fruitful year (2019) in private enforcement rulings with an important one in terms of “who” is entitled to be compensated for damages caused by competition law infringements: the Otis of 12 December 2019 (C-435/18). It ruled that any damage which has a causal connection with an infringement of Article 101 of the Treaty on the Functioning of the European Union (TFEU) must be capable of giving rise to compensation even if the injured party does not operate in the market affected. Despite the abstract character of this statement, which leaves a large margin of application for national courts – and therefore of legal uncertainty –, the ECJ is (once again) coming out in defense of the principle of the effectiveness of EU competition rules and taking over the competence to determine the substantive part of private enforcement, i.e., the liability requirements.